Penguatan Karakter Anak Usia Dini Melalui Bimbingan dan Konseling - Rozikan, Muhamad (STKIP Muhammadiyah Pringsewu, 2018)
The existence of Early Childhood Education is not only so that children are better prepared to learn at the elementary school level but so that children get intellectual, social, and emotional stimuli according to their age level. The existence of guidance and counseling in the Age of Education is needed because many problematic behaviors arise in students when they are adults caused by their past childhood. The main purpose of holding guidance and counseling in Early Childhood Education is to anticipate or take preventive action against the emergence of problematic behavior.Â Keywords:Â the character of early childhood, guidance and counseling.